AMINA WADUD’S THOUGHTS ON THE BOOK OF TAFSIR QUR’AN AND WOMEN - nugraha, Fajar; Tsaltsani Oktasajidah; Muhyi Sobri (UIN Mataram, 2025)
interpretation, particularly in her book ‘Qur'an and Women’. She asserts that restrictions on women do not come from the Qur'anic text itself, but from interpretations of religious texts that are often gender-biased. Amina Wadud argues that it is not the Qur'anic text that restricts women, but the interpretation of religious texts that are often considered more important than the Qur'an itself. By using a hermeneutic methodology approach, Amina Wadud emphasises objectivity rather than subjectivity to facilitate the interpretation of Qur'anic verses, especially on gender issues. She fights for equal responsibility between men and women without ignoring the important differences between them. This research was conducted using the literature study method, using primary sources from Amina Wadud's works and related secondary sources. The results of this study show that Amina Wadud's thought brings a new perspective in Qur'anic interpretation that is more inclusive of women, challenging classical interpretations that tend to limit the role of women in Islam.